Hadith Review of the Phenomenon of Catcalling in the Public Sphere - Irfan Padlian Syah; Muhammad Alif (International Journal of Islamic Educational Research, 2025)
Catcalling, also known as street harassment, is a form of sexual harassment that occurs in public places. This form of harassment usually takes the form of unwanted, sexual, provocative or degrading comments or statements, and is often directed at other people, especially women. Many believe that catcalling is something common and normal, some even consider it a compliment or joke that usually occurs in public places. This research adopts a qualitative approach, collecting main data from hadiths contained in digital collections such as Maktabah Syamilah, Hadith Soft, and Hadith Encyclopedia Buku 9 Imams. Secondary data sources include literature related to catcalling cases. Data was collected through library research. This research uses thematic methods to analyze contemporary hadiths and applies grounded theory methods. This research reveals that catcalling has two types, namely verbal and non-verbal. The perpetrator often says words with the aim of teasing. And there are several precautions that we must take to prevent catcalling. These include guarding your words and actions, having the principles of ukhuwwah Islamiyyah, being silent, and not sitting on the side of the road.